PENGARUH PERSEPSI GURU TENTANG SUPERVISI KEPALA SEKOLAH, IKLIM KERJA, DAN PROFESIONALISME GURU TERHADAP MOTIVASI KERJA GURU DI SMP NEGERI SUB RAYON 02 MUNTILAN KABUPATEN MAGELANG - Nugrahantini , Nanik Istantri (2011)
The purpose of this research are (1) to assess the influence of teacher 'perception about leadership supervision, working climate, and teacher's professionalism towards work motivation of teacher at The Goverment Junior High Schools of Sub District 02 Muntilan in Magelang Regency, (2) to assess the influence of teachers' perceptions about leadership supervision towards work motivation of teachers at The Goverment Junior High Schools of Sub District 02 Muntilan in Magelang Regency, (3) to assess the influence of working climate towards work motivation of teachers at The Goverment Junior High Schools of Sub District 02 Muntilan in Magelang Regency, and (4) to assess the influence of professionalism teachers towards work motivation of teachers at The Goverment Junior High Schools of Sub District 02 Muntilan in Magelang Regency. The population in this research are all The Goverment Junior High Schools teacher of Sub District 02 Muntilan in Magelang Regency. Total population is 175 teachers with 5% error rate in their sample size is obtained based on Table Krecie 117. Determination of sampling of this research with a sample random sampling. Engineering data analysis by multiple linear regression analysis with the prerequisite test. The results showed (1) there is significant influence teacher perception about leadership supervision, working climate, and professionalism of teacher towards work motivation of teacher at The Goverment Junior High Schools of Sub District 02 Muntilan in Magelang Regency, indicated by the obtained F value was 66.673 with a level of significance = 0.000 <0.005. Coefficient of determination (R2 ) is 0.639, meaning that the amount of donations given by the teachers' perceptions about leadership supervision, working climate, and the professionalism of teachers towards work motivation of teachers at The Goverment Junior High Schools of Sub District 02 Muntilan in Magelang Regency is 63.9%, (2 ) there is significant influence teachers' perceptions about leadership supervision towards work motivation of teachers at The Goverment Junior High Schools of Sub District 02 Muntilan in Magelang Regency, with the obtained value of t 4.726 and p = 0.000 <0.05; (3) there is significant influence of working climate towards work motivation of teachers at The Goverment Junior High Schools of Sub District 02 Muntilan in Magelang Regency, with the obtained value of t 5.287 and p = 0.000 <0.05, and (4) there is significant influence teachers professionalism towards work motivation of teacher at The Goverment Junior High Schools of Sub District 02 Muntilan in Magelang Regency, with obtained value of 5.177 and p = 0.000 <0.05.